Reproductions of Banality : Fascism, Literature, and French Intellectual Life - Kaplan, Alice Yaeger (Book collections on Project MUSE., 1986)
Reproductions of Banality was first published in 1986. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. An established fascist state has never existed in France, and after World War II there was a tendency to blame the Nazi Occupation for the presence of fascists within the country. Yet the memory of fascism within their ranks still haunts French intellectuals, and questions about a French version of fascist ideology have returned to the political forefr.